2023
DOI: 10.1101/2023.10.17.562770
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Skimming genomes for systematics and DNA barcodes of corals

Andrea M. Quattrini,
Luke J. McCartin,
Erin E. Easton
et al.

Abstract: 1: Numerous genomic methods developed over the past two decades have enabled the discovery and extraction of orthologous loci to help resolve phylogenetic relationships across various taxa and scales. Genome skimming (or low-coverage whole genome sequencing) remains a low-cost, promising method to not only extract high-copy loci, but also 100s to 1000s of phylogenetically informative single-copy nuclear loci (e.g., ultraconserved elements [UCEs] and exons) from contemporary and historical museum samples. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Many of these problematic cases, especially within the black corals, reflect incongruences between phylogenetic relationships and taxonomic nomenclature rather than the rate of evolution of the 28S barcode and its ability to distinguish taxonomic identity at the genus level. In black corals, phylogenetic evidence suggests that the genera Stichopathes and Cirrhipathes are polyphyletic (Bo et al 2018, Quattrini et al 2023). Likewise, Barret et al (2020) suggested that validations of the genera within Schizopathidae and Cladopathidae are necessary based on mitochondrial genome sequencing data.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many of these problematic cases, especially within the black corals, reflect incongruences between phylogenetic relationships and taxonomic nomenclature rather than the rate of evolution of the 28S barcode and its ability to distinguish taxonomic identity at the genus level. In black corals, phylogenetic evidence suggests that the genera Stichopathes and Cirrhipathes are polyphyletic (Bo et al 2018, Quattrini et al 2023). Likewise, Barret et al (2020) suggested that validations of the genera within Schizopathidae and Cladopathidae are necessary based on mitochondrial genome sequencing data.…”
Section: Resultsmentioning
confidence: 99%
“…Low coverage whole-genome sequencing (genome skimming) data were generated from specimens collected in the Gulf of Mexico following the methods described by Quattrini et al (2023). Several of these specimens were also barcoded with Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within Scleralcyonacea, the sister group to the Keratoisididae-Isidoidae clade is either Chrysogorgiidae or Primnoidae depending on whether the inference was constructed using nuclear or complete mitochondrial genomes respectively ). The ever-reducing cost of nextgeneration sequencing, and the ability to mine Sequence Read Archives (SRAs) for mitogenomic data (e.g., Muthye et al 2022;Hogan et al 2023) and conserved elements (Quattrini et al 2023a) will enable more comprehensive studies that can compare between alternative evolutionary histories and better explore the reasons as to why this discordance exists.…”
Section: Introductionmentioning
confidence: 99%